A Spatial Analysis of Acute Myocardial Infarction Rates in New York State in Relation to Hospitals Along State Jurisdictional Borders. (September 2017) - Stamm, Abigail J.; Savadatti, Sanghamitra S.; Kumar, Sanjaya; Hwang, Syni-An
Abstract : Introduction: Patients experiencing acute myocardial infarction (AMI) are likely to visit the nearest hospital providing appropriate services since timely care is a critical determinant in the treatment and progression of AMI. We comparatively examined AMI rates in border and nonborder census tracts. The New York State (NYS) Environmental Public Health Tracking (EPHT) program, in conjunction with the Statewide Planning and Research Cooperative System, will work on developing memoranda of understanding with neighboring states to be able to more comprehensively access NYS residents' out-of-state health records. Objective: To determine whether AMI rates in the NYS border census tracts differ from AMI rates in nonborder census tracts as a preliminary exploration of the utilization of out-of-state care for acute health conditions by NYS border residents. Design: We reviewed data on inpatient and emergency department visits in NYS with discharge dates from 2005 to 2014 retrospectively. We used the NYS EPHT tier 1 system database to locate hospitals. We geocoded all cases to NYS 2010 census tracts. We mapped differences between border and nonborder tracts and analyzed resulting spatial patterns. We computed tract-level AMI rates and differences between border and nonborder AMI rates. Results: The age-adjusted AMI rates differed by 8.2 cases per 10 000 people (95% confidence interval, 6.94-12.60). Maps showed patterns of differences in AMI rates, especially along the NYS border with New England and other geographically closer out-of-state hospitals. Conclusions: AMI rates that were geographically closer to out-of-state hospitals were lower, suggesting that people residing in border census tracts are utilizing out-of-state care. Our study adds to literature on the geographical component of health care accessibility and utilization in the context of acute conditions such as AMI and lends impetus to access out-of-state health records to better understand health care facility access and utilization for NYS residents. Abstract : Supplemental Digital Content is Available in the Text.